PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS PADI GOGO TERHADAP PEMBERIAN PUPUK ORGANIK CAIR - Ellya Ekaristi Tarigan; Jonis Ginting; Meiriani Meiriani (Universitas Sumatera Utara, 2013)
ABSTRACTGrowth and Production Some Varieties of Upland Rice with Application Liquid Organic Fertilizer.This research aims to study the growth and production of some varieties of upland rice to liquidorganic fertilizer. The research was conducted in the field UPT BBI, Tanjung Selamat at an altitude± 57 meters above sea level since May 2012 until August 2012 using Randomized Block Design(RBD) factorial with two factors, which are the varieties (Situ Bagendit, Situ Patenggang andTowuti) and liquid organic fertilizer (0, 10, 20, 30 cc/liter). The parameters measured were plantheight, number of tillers, number of panicle, number of empty grain, the amount of grainproductive, productive grain weight, grain 1000 grain weight, and grain production per plot. Theresults showed that the treatment of varieties significantly affect of plant height, number of tillers,number of panicle, productive grain weight, grain 1000 grain weight, and grain production per plot.Liquid organic fertilizer non significant affect to all of parameters. The interaction between thevarieties and liquid organic fertilizer non significant affect to all of the parameters.Keywords: varieties, liquid organic fertilizer, upland rice